Dopa derivative, preparation method thereof and application of dopa derivative in preparation of dynamic super-hydrophilic implant

By developing dopa derivatives with copper-free click reactive groups and adjustable valence number characteristics, various shortcomings of existing superhydrophilic surface modification methods have been solved, compatibility with a variety of substrate materials and diversified properties of functional materials have been achieved, and suitable for a variety of medical and bioengineering applications.

CN119529021APending Publication Date: 2025-02-28SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411715315.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing superhydrophilic surface modification methods have problems such as surface inhomogeneity, material damage, material selection limitations, poor stability and biocompatibility, which are difficult to meet the needs of various application scenarios.

Method used

A dopa derivative was developed with copper-free click reactive groups and adjustable valence characteristics, able to closely bind to a variety of substrate materials, and functional materials with diversified properties were prepared through molecular grafting technology.

Benefits of technology

It achieves extensive compatibility and close integration with a variety of substrate materials, can flexibly adjust the hydrophilicity and other properties of the materials, and is suitable for a variety of medical and bioengineering applications, improving the binding strength and biocompatibility of the implant and host bone tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529021A_ABST
    Figure CN119529021A_ABST
Patent Text Reader

Abstract

The invention discloses a dopa derivative, a preparation method thereof and an application of the dopa derivative in preparation of a dynamic super-hydrophilic implant, the dopa derivative has the following structural formula: # imgabs0 #, in the formula, R0 is selected from a group capable of generating a copper-free click chemical reaction; r1 is selected from AcNH <->; a is an integer selected from 2 to 6; and b is selected from an integer of 1-6. The dopa derivative designed by the invention has the potential of serving as an efficient binder, and can be widely and tightly combined with various types of substrate materials, so that the dopa derivative can be flexibly applied to diversified scenes due to the characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical biomaterials, and in particular to a dopa derivative and a preparation method thereof and an application thereof in preparing a dynamic super-hydrophilic implant. Background Art

[0002] In the process of clinical bone implant treatment, the success of the implant is closely related to the surface interface properties of its material. In order to improve biocompatibility and promote the bone integration of implants, researchers have proposed the concept of superhydrophilic surface interface. This superhydrophilic surface can significantly enhance the adhesion, proliferation and differentiation ability of osteoblasts, thereby promoting the generation and repair process of bone tissue. In addition, the surface interface properties can also provide a microenvironment that is conducive to the regulation of cell behavior, thereby accelerating the overall bone integration process.

[0003] The traditional preparation methods of superhydrophilic implants mainly include: ① Mechanical treatment: using oxide particles (such as corundum and silica sand) through sandblasting technology to obtain a rough surface morphology and increase the wettability of the material. Sandblasting is often used to activate the surface of materials and is often used in combination with other surface active methods. For example, patent document CN112974843A describes a surface treatment process for 3D printed implants, including laser selective melting, sandblasting, acid etching and electropolishing oxidation treatment to obtain implants with high biosafety, excellent bone bonding and good mechanical properties. ② Etching treatment: Common chemical etching treatment methods include pickling, alkali treatment, passivation treatment and hydrogen peroxide treatment. For example, Straumann's patent document WO2016189097A1 describes etching using a mixed solution of inorganic acids (HCl and H2SO4) and hydrofluoric acid to improve blood coagulation and / or cell attachment on titanium or titanium alloy parts. Other common chemical treatment solutions include phytic acid / calcium hydroxide mixed solution (see patent document CN106823005A), NaOH or KOH solution and hydrogen peroxide solution (see patent document WO2010102254A2). ③ Anodization: As described in Nobel Biocare's patent document WO2015132325A1, the implant is immersed in a container containing electrolytes (sulfuric acid and phosphoric acid) and a voltage of 30-100 volts is applied to obtain an anatase phase outer surface to reduce microbial colonization. ④ Glow discharge plasma treatment: In an ultra-high vacuum environment (<10 - 7Pa), through the high potential difference between the two electrodes (about 1kV, DC or AC) to partially ionize the gas, affect the processed material, and achieve the purpose of cleaning the surface interface, increasing surface energy and wettability. ⑤ Laser etching: As described in patent document WO2013124693A1, in air containing 85% nitrogen, a 30kHz frequency laser is used with continuous pulses (1ps-100ns) to change the surface morphology and chemical properties of the implanted material, increase the roughness and improve the contact angle of water, and promote superhydrophilicity.

[0004] In addition, superhydrophilicity can also be enhanced by chemical group modification treatment, such as introducing hydrophilic molecules (such as zwitterions, polyethyleneimine, etc.) on the surface of the implant, which can be fixed on the surface by covalent bonds or physical adsorption to form a stable hydrophilic layer. Osstem's patent documents describe methods for obtaining superhydrophilic properties using buffer treatment, including UV irradiation combined with buffer (sulfonic acid group (BES, HEPES, MOPS or TES)) treatment and pretreatment disclosed in patent document WO2013165051A1, so that the amphoteric organic compound on the implant surface reacts with the sulfonic acid group; patent document WO2014175657A1 discloses the use of pre-treatment of the implant surface, and then coating the implant surface with a mixture of an organic or inorganic pH buffer substance and an organic amphoteric substance having a sulfone group.

[0005] Although these methods have made significant progress in promoting the application of superhydrophilic materials in clinical bone implant treatment, the existing surface modification methods still face a series of defects and deficiencies that need to be solved. However, these methods also have some defects and deficiencies: ① Surface unevenness: The surface roughness of the modified material may be uneven, which may affect the consistency and stability of the superhydrophilic performance, thereby affecting the later bone healing. ② Material damage: The material itself may be damaged during mechanical treatment, forming tiny cracks, affecting the mechanical properties of the material. ③ Material selection restrictions: Not all materials are suitable for surface modification treatments such as sandblasting and acid etching, and the scope of application is limited. At the same time, different application scenarios have different requirements for superhydrophilicity. For example, in the repair of the extracellular matrix of articular cartilage, traditional methods often lack flexibility and are difficult to meet certain specific needs. ④ Poor stability: Traditional modification methods may cause the superhydrophilicity of the surface interface to decrease over time, especially in humid or easily contaminated biological environments, thereby affecting the adhesion and aggregation of osteoblasts. ⑤ Biocompatibility: Different surface modification methods will affect the biocompatibility of the material.

[0006] In summary, existing surface modification methods such as superhydrophilicity still have many shortcomings and urgently need new technological breakthroughs and innovations. Therefore, it is of great significance to develop a new material that is widely compatible with and firmly bonded to various substrate materials. At the same time, according to specific application requirements, hydrophilicity and other functions can be flexibly modified to be suitable for a variety of scenarios. In the medical field, especially in clinical bone implant treatment, the application of this new material is expected to significantly improve the bonding strength and biocompatibility between the implant and the host bone tissue, thereby promoting the optimization of treatment effects, reducing complications, and accelerating the patient's recovery process. Summary of the invention

[0007] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, in a first aspect of the present invention, a dopa derivative is provided.

[0008] The second aspect of the present invention provides a method for preparing the above derivatives.

[0009] The third aspect of the present invention provides a functional material prepared using the above derivatives.

[0010] The fourth aspect of the present invention provides the use of the above derivatives and functional materials in implants.

[0011] According to a fifth aspect of the present invention, a method for preparing the above implant is provided.

[0012] A sixth aspect of the present invention provides the application of the above implant.

[0013] The dopa derivative according to the first aspect of the present invention has the following structural formula:

[0014]

[0015] In the formula, R0 is selected from a group capable of undergoing a copper-free click reaction; R1 is selected from AcNH-; a is selected from an integer of 2 to 6; and b is selected from an integer of 1 to 6.

[0016] According to the embodiments of the present invention, the DOPA derivatives have at least the following beneficial effects: the DOPA derivatives designed by the present invention have the potential to be used as efficient adhesives, and can be widely and tightly combined with various types of substrate materials. This characteristic enables the DOPA derivatives to be flexibly applied to diversified scenarios. More importantly, the molecular structure design of the DOPA derivative is unique, and a group capable of copper-free click reaction is specially introduced at its end. This functional modification provides the possibility for subsequent molecular grafting. Through this characteristic, a wide variety of molecules can be grafted, and customized molecular materials with diversified properties can be prepared (such as grafting superhydrophilic molecules to prepare hydrophilic implants, etc., and introducing specific antibacterial molecules into antibacterial coatings), which greatly broadens the application range and functional properties of the materials. In addition, the valence of the DOPA derivatives, that is, the number of active sites in its molecules that can interact with other molecular modules, can be adjusted to achieve precise assembly with molecular modules of different valences. This assembly strategy not only enhances the controllability of the material structure, but also can carefully adjust the overall performance level of the material according to actual needs, such as the strength of hydrophilicity, so as to meet the high performance requirements in specific application scenarios.

[0017] In summary, the DOPA derivatives in the scheme of the present invention provide strong technical support for the development of high-performance and multifunctional new materials by virtue of their wide applicability as binders, molecular grafting ability mediated by azide groups, and molecular assembly characteristics with adjustable valence.

[0018] According to some embodiments of the present invention, a is selected from integers of 2-4.

[0019] According to some embodiments of the present invention, b is selected from an integer of 1-2.

[0020] According to some embodiments of the present invention, R0 is selected from at least one of an azido group or a nitrile oxide, and can be an azido group or a nitrile oxide-based click reaction, a 1,3-dipolar cycloaddition reaction with an alkyne or an alkene, or other groups capable of copper-free click reaction.

[0021] According to some embodiments of the present invention, the DOPA derivative has one of the following structural formulas:

[0022]

[0023] The preparation method according to the second aspect of the present invention comprises the following steps:

[0024] S1, reacting compound C containing an amino protecting group R4 with compound D to obtain intermediate 1, and removing the amino protecting group R4 in the intermediate to obtain intermediate 2;

[0025] S2, adding compound C to react intermediate 2 with compound C;

[0026] S3, repeat the operation of step S2 c times;

[0027] S4, after acetylation reaction and removal of the propylidene group, the DOPA derivative is obtained;

[0028] Wherein, the structural formula of compound C containing amino protecting group R4 is as follows:

[0029]

[0030] The structural formula of compound D is as follows:

[0031]

[0032] c=a-2.

[0033] The preparation method according to the embodiment of the present invention has at least the following beneficial effects: the preparation method of the scheme of the present invention is easy to operate and has good industrial application prospects.

[0034] According to some embodiments of the invention, R3 is selected from at least one of Fmoc (fluorenylmethoxycarbonyl), Alloc (allyloxycarbonyl) or Teoc (trimethylsilylethoxycarbonyl).

[0035] According to some embodiments of the present invention, the preparation process of intermediate 1 in step S1 specifically includes: taking a solution containing compound C, adding compound D and 4-dimethylaminopyridine, mixing, and then adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to obtain intermediate 1.

[0036] According to some embodiments of the present invention, the specific operation of removing the amino protecting group in step S1 includes: mixing the intermediate 1 with an organic solvent (such as N,N-dimethylformamide (DMF) or CH2Cl2 (DCM)), adding an organic amine compound (such as triethylamine (Et3N) or piperidine) to remove the amino protecting group in the intermediate 1.

[0037] According to some embodiments of the present invention, the specific operation of step S2 includes: mixing a solution containing intermediate 2 with a solution containing compound C, and reacting them, wherein the solution containing intermediate 2 also contains an organic solvent (such as CH2Cl2 (DCM) etc.) and an organic amine compound (triethylamine (Et3N)), and the solution containing compound C also contains an organic solvent (such as CH2Cl2 (DCM) etc.), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole (HoBT).

[0038] According to some embodiments of the present invention, in step S4, acetylation reaction is achieved by adding acetic anhydride under the condition of pyridine as solvent.

[0039] According to some embodiments of the present invention, in step S4, trifluoroacetic acid is added under the condition of dichloromethane as solvent to achieve the depropylidene group reaction.

[0040] According to the functional material of the third aspect of the present invention, the raw materials for preparing the functional material include compound A, and the compound A is the above-mentioned dopa derivative.

[0041] According to some embodiments of the present invention, the raw material for preparing the functional material further includes compound B, and the compound B has the following structural formula:

[0042]

[0043] In the formula, R2 is a group that can undergo copper-free click chemistry reaction with R0; R3 is selected from an alkylene group (preferably, having 1 to 15 carbon atoms), an alkylene group containing an amide bond (preferably, having 1 to 15 carbon atoms), a PEG containing an amide bond (preferably, the number of repeating units of PEG is 1 to 5), or d is selected from an integer of 1-4, and e is selected from an integer of 1-5.

[0044] According to some embodiments of the present invention, R2 is selected from dibenzocyclooctyne (DBCO), diaryl azacyclooctanone (BARAC), bifunctional fluorinated cyclooctyne or cyclooctyne. In addition to DBCO, R2 can also be diaryl azacyclooctanone (BARAC), which is used for labeling azide; or bifunctional fluorinated cyclooctyne, which can be used to achieve in situ "click" chemical cross-linking of azide groups; in addition, R2 can also be cyclooctyne, which can react rapidly with azide to generate triazole compounds.

[0045] According to some embodiments of the present invention, the compound B has one of the following structural formulas:

[0046]

[0047] The DOPA derivatives of the present invention can be grafted with compound B (PC super-hydrophilic module) to form super-hydrophilic molecules, and can also be grafted with other molecular modules to meet the needs of different application scenarios by cross-linking with diverse molecular structures. For example: introducing specific antibacterial molecules into antibacterial coatings. This allows the DOPA derivatives of the present invention to achieve a wider range of functional applications. The DOPA derivatives of the present invention not only break through the limitations of traditional materials, but also provide new ideas and possibilities for the design of multifunctional coatings and composite materials.

[0048] According to some embodiments of the present invention, the molar ratio of compound A to compound B in the raw material for preparing the functional material is 1 to 4:1.

[0049] According to the implant of the fourth aspect of the present invention, the implant comprises the above-mentioned dopa derivative or functional material.

[0050] According to some embodiments of the present invention, raw materials for preparing the implant include a base material and a functional material.

[0051] According to some embodiments of the present invention, the base material includes at least one of a polymer-based material, a ceramic-based material, and a metal-based material.

[0052] According to some embodiments of the present invention, the polymer-based material includes at least one of polyetheretherketone (PEEK), polyurethane (Polyurethane), polyethylene (Polyethylene) or polylactic acid (PLA).

[0053] According to some embodiments of the present invention, the ceramic-based material comprises at least one of silicon nitride ceramic or bioactive glass ceramic.

[0054] According to some embodiments of the present invention, the metal-based material includes metals and their alloys, metal oxides, and the like.

[0055] According to some embodiments of the present invention, the metal-based material includes at least one of aluminum, titanium, tantalum, magnesium, cobalt-chromium alloy, magnesium alloy, titanium alloy or titanium dioxide.

[0056] The functional material molecules of the scheme of the present invention can be combined with a variety of different bone implant substrate materials, so it has scalability on bone implant substrate materials, specifically including but not limited to the following categories: ① Polymer substrate: Applying functional materials as super-hydrophilic coatings on the surface of polymers (such as polyetheretherketone, etc.) can improve their surface wettability, promote cell attachment and growth, and be suitable for soft tissue engineering, etc.; ② Ceramic materials: For ceramic implants in dental and orthopedic applications, the functional materials of the scheme of the present invention can also be attached to their surfaces as super-hydrophilic coatings; ③ Other metal substrates: The functional materials of the scheme of the present invention can also be applied to other metal-based materials such as aluminum and cobalt-chromium alloys to improve their surface properties and expand their application potential in the fields of medicine and bioengineering.

[0057] According to the preparation method 1 of the fifth aspect of the present invention, the raw materials for preparing the implant include a base material, compound A and compound B, and the preparation method includes the following steps:

[0058] S1, taking a base material, placing the base material in a solution containing compound A, reacting to obtain an intermediate material;

[0059] S2, adding a solution containing compound B to allow compound B to undergo a click chemical reaction with molecular groups on the surface of the intermediate material to obtain the implant;

[0060] Wherein, the compound A is the above-mentioned DOPA derivative, and the compound B has the following structural formula:

[0061]

[0062] In the formula, R2 is a group that can undergo copper-free click chemistry reaction with R0; R3 is selected from alkylene, alkylene containing amide bonds, PEG containing amide bonds, or d is selected from an integer of 1-4, and e is selected from an integer of 1-5.

[0063] According to some embodiments of the present invention, the solvents in the solution containing compound A and the solution containing compound B are independently selected from at least one of water, buffered saline solution or dimethyl sulfoxide.

[0064] According to some embodiments of the present invention, the concentration of the solute in the solution containing compound A and the solution containing compound B is independently selected from 0.01 mg / mL to 1.0 mg / mL, such as 0.1 mg / mL.

[0065] According to some embodiments of the present invention, the reaction time of step S1 is 2 to 6 hours, such as 4 hours.

[0066] According to some embodiments of the present invention, the reaction time of step S2 is 20 to 36 hours.

[0067] According to the second preparation method of the fifth aspect of the present invention, the raw materials for preparing the implant include a base material and the above-mentioned functional material, and the preparation method includes the following steps: placing the base material in a solution containing the functional material, reacting, and obtaining the implant.

[0068] The implant can be prepared by a one-step method or a two-step method, and the operation is flexible.

[0069] According to some embodiments of the present invention, the preparation method further comprises pretreating the substrate material.

[0070] According to some embodiments of the present invention, the base material is a titanium base material, and the pretreatment is grinding to a mesh size of 500 to 3000.

[0071] According to some embodiments of the present invention, the pretreatment is a sandpaper polishing treatment for 5-20 minutes.

[0072] According to some embodiments of the present invention, all reaction temperatures in the implant preparation process are independently selected from 20 to 30° C. The reaction can be carried out at room temperature without heating, with mild conditions, simple operation, and energy saving.

[0073] According to some embodiments of the present invention, the reaction time of the base material in the solution containing the functional material is 24 to 36 hours.

[0074] According to the application of the sixth aspect of the present invention, an orthopedic titanium medical device is provided, comprising a titanium-based material and a functional material, wherein the titanium-based material comprises at least one of titanium, titanium alloy or titanium dioxide.

[0075] In the description of the present invention, the “—” at the end of R1 and R3 represents a connection site.

[0076] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0078] Figure 1 This is a schematic diagram of the raw material structure for preparing the functional materials in Examples 4 to 5 of the present invention.

[0079] Figure 2 Schematic diagram of the structure of the titanium implant in Examples 6 to 10 of the present invention.

[0080] Figure 3This is an operational flow chart of the one-step synthesis of super-hydrophilic coatings on titanium implants in Examples 6 to 10 of the present invention.

[0081] Figure 4 This is an operational flow chart of the two-step synthesis of super-hydrophilic coatings on titanium implants in Examples 6 to 10 of the present invention.

[0082] Figure 5 This is a graph showing the contact angle test results of the titanium implant surface prepared in Example 10 of the present invention.

[0083] Figure 6 This is a statistical graph of the contact angle test results of the titanium implant surfaces prepared in Examples 6 to 10 of the present invention.

[0084] Figure 7 This is a graph showing the expression results of osteogenesis-related genes (ALP, OPN and Runx2) in the test example of the present invention. DETAILED DESCRIPTION

[0085] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0086] In the description of the present invention, the description with reference to the term "some embodiments" or the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0087] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0088] The "room temperature" referred to in the present invention refers to 25±5°C, and is specifically 25°C in the embodiments.

[0089] The “stirring” referred to in the embodiments of the present invention refers to stirring at a rotation speed of 600 rpm.

[0090] Example 1

[0091] This example provides a dopa derivative, the structural formula of which is as follows:

[0092]

[0093] Its synthetic route is as follows:

[0094]

[0095] The specific synthesis process is:

[0096] 1. Synthesis of chemical molecule 2a

[0097] In water, add 1a (5g, 1eq) and sodium bicarbonate (10.65g, 5eq) into a flask and stir at room temperature for 10 minutes. 9-Fluorenylmethyl-N-succinimidyl carbonate (11.2g, 1.3eq) is dissolved in 1.4-dioxane (75ml), added dropwise into the flask using a separatory funnel, and stirred at room temperature for 20 hours. The reaction solution is washed with n-hexane, and 250ml of water is added, and the aqueous phase is collected with a separatory funnel. The aqueous phase is adjusted to pH 3 with hydrochloric acid (1M), and ethyl acetate is added, and the organic layer is separated, dried over Na2SO4, and the solvent is evaporated to obtain the crude product 2a without purification. The product is 10.1g, with a yield of 95%, and ESI-MS m / z calcd for [C 24 H 22 NO6] + (M+H) + :420.14,found:420.13.

[0098] 2. Synthesis of chemical molecule 3a

[0099] Take 2a (10.46g, 1eq) and dissolve it in N,N-dimethylformamide (100ml) and K2CO3 (3.5g, 1eq), put it in an ice bath at 0℃, stir it for 10 minutes, and add benzyl bromide (3ml, 1.1eq) dropwise using a constant pressure funnel. The reaction mixture is cooled to room temperature and stirred for 17 hours. Evaporate the solvent, dissolve the residue in ethyl acetate, wash it with water, collect the organic phase, dry it with Na2SO4, evaporate the solvent to obtain the crude product 3a, and purify it by HPLC (gel permeation chromatography). The product is 11.63g, with a yield of 90%, and ESI-MS m / z calcd for [C 31 H 28 NO6] + (M+H) + :510.18,found:510.20.

[0100] 3. Synthesis of chemical molecule 4a

[0101] 3a (6.3 g, 1 eq) was dissolved in 2,2-dimethoxypropane (19.31 g, 15 eq), and p-toluenesulfonic acid (212 mg, 0.1 eq) was added for catalysis. The mixture was stirred at 80°C in an oil bath for 36 hours. Triethylamine (10 mml) was added to adjust the pH to neutral. The solvent was evaporated to obtain the crude product 4a, which was purified by HPLC (gel permeation chromatography). The product was 5.78 g, with a yield of 85%. ESI-MS m / z calculated for [C 34 H 32 NO6] + (M+H) + :550.22,found:550,31.

[0102] 4. Synthesis of chemical molecule 5a

[0103] 4a (6.8 g, 1 eq) was dissolved in tetrahydrofuran (100 ml) and palladium / carbon (0.5 g) was added. The mixture was stirred in a hydrogenation apparatus for 16 hours. The solution was filtered and the solvent was evaporated to obtain the crude product 5a, which did not need to be purified. The product was 5.68 g, with a yield of 100%. ESI-MS m / z calculated for [C 27 H 26 NO6] + (M+H) + :450.17,found:450.18.

[0104] 5. Synthesis of chemical molecule 6a

[0105] Take 5a (790 mg, 1.5 eq) and dissolve it in dichloromethane (10 ml). Add 1-amino-11-azido-3,6,9-trioxaundecane (250 mg, 1 eq) and 4-dimethylaminopyridine (28 mg, 0.2 eq). Stir at room temperature for 10 minutes. Then add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (440 mg, 2 eq) and stir at room temperature for 1 hour. The solvent is evaporated to obtain the crude product 6a, which is purified by HPLC (gel permeation chromatography). The product is 1.02 g, with a yield of 96%. ESI-MS m / z calculated for [C 33 H 38 N5O7] + (M+H) + :616.27,found:617.30.

[0106] The synthetic cycle route is as follows:

[0107]

[0108] 6. Synthesis of chemical molecule 7a

[0109] 6a (1 g) was dissolved in triethylamine and dichloromethane (V / V = 1:1), stirred at room temperature for 24 hours, and the solvent was evaporated to obtain the crude product 7a without purification. The product was 639.03 mg, with a yield of 100%. ESI-MS m / z calculated for [C 18 H 28 N5O5] + (M+H) + :394.20,found:394.23.

[0110] 7. Synthesis of chemical molecule 8a

[0111] 5a (600 mg, 1.2 eq) was dissolved in dichloromethane (20 ml), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (312.9 mg, 1.5 eq) and 1-hydroxybenzotriazole (220.5 mg, 1.5 eq) were added, and the mixture was stirred at room temperature for 15 minutes. 7a (476 mg, 1 eq) was dissolved in dichloromethane (20 ml) and triethylamine (330.3 mg, 3 eq), and the above 5a solution was added dropwise under an ice bath at 0°C, and stirred at 0°C for 2 hours. The solvent was evaporated, the residue was dissolved in dichloromethane, washed with water, the organic phase was collected, dried over Na2SO4, and the crude product 8a was obtained by evaporation of the solvent and purified by HPLC (gel permeation chromatography). The product was 623.87 mg, with a yield of 80%, and ESI-MS m / z calculated for [C30H 41 N6O8] + (M+H) + :613.26,found:613.28.

[0112] 8. Synthesis of chemical molecule DOPA2-N3

[0113] Take 8a (600 mg; 1 eq) and dissolve it in 5 ml of pyridine. Slowly add 2 ml of acetic anhydride and stir in an ice bath at 0°C for 1 hour. Add 3 ml of methanol to quench the reaction and stir in an ice bath for 15 minutes. The solution was evaporated to dryness, the residue was dissolved in dichloromethane, acetic acid (0.5 mmol) was added to adjust the organic phase to neutrality, and the solution was evaporated to dryness. Prepare a solution of trifluoroacetic acid / anhydrous methanol / water / dichloromethane = 30:2.5:2.5:65, stir at room temperature for 30-40 minutes, and evaporate the solvent to obtain the crude DOPA2-N3 product without purification. The product is 472.97 mg, with a yield of 75%. ESI-MS m / z calcd for [C 26 H 35 N6O9] + (M+H) + :575.24,found:575.25.

[0114] Example 2

[0115] This example provides a dopa derivative, the structural formula of which is as follows:

[0116]

[0117] Its synthetic route is as follows:

[0118]

[0119] The specific preparation process is basically the same as that of Example 1, except that after repeating the cycle once, a crude product of NH2-(DOPA)3-PEG2-N3 is obtained with a yield of 80%. ESI-MS m / z calculated for [C 42 H 54 N7O 11 ] + (M+H) + :834.38, found:834.39. Similarly to Example 1, after acetylation and depropylation, a crude product of DOPA3-N3 was obtained with a yield of 80%. ESI-MS m / z calculated for [C 33 H 42 N7O 11 ] + (M+H) + :712.29,found:712.30.

[0120] Example 3

[0121] This example provides a dopa derivative, the structural formula of which is as follows:

[0122]

[0123] Its synthetic route is as follows:

[0124]

[0125] The specific preparation process is basically the same as that of Example 1, except that after two cycles, the crude product NH2-(DOPA)4-PEG2-N3 is obtained with a yield of 80%. ESI-MS m / z calculated for [C 54 H 67 N8O 14 ] + (M+H) +:1051.47, found:1051.45. Similarly to Example 1, after acetylation and depropylation, a crude product of DOPA4-N3 was obtained with a yield of 80%. ESI-MS m / z calculated for [C 42 H 51 N8O 14 ] + (M+H) + :891.34,found:891.35.

[0126] Example 4

[0127] This example provides a functional material, which is prepared from a grafting module and a functional module, and the two are combined through the grafting module and the connecting module in the functional module, such as Figure 1 As shown, the grafting module is composed of DOPA derivatives, wherein the valence of a single grafting module ranges from 1 to 5; the functional module is a superhydrophilic module, composed of PC molecules, wherein the valence of a single superhydrophilic module ranges from 1 to 5; the connecting module is a Click reactive group, which can be a cycloaddition reaction, non-alcohol aldehyde carbonyl chemistry, and carbon-carbon multiple bond addition reaction.

[0128] Specifically, the raw materials for preparing the functional material of this example are composed of compound A and compound B, wherein compound A is the grafting module, which is the DOPA derivative prepared in the above examples 1 to 3; compound B is the functional module, and its structural formula is as follows:

[0129]

[0130] The preparation route is as follows:

[0131]

[0132] 1. Synthesis of chemical molecule 2b

[0133] Compound 1b (1 g, 1 eq) was dissolved in tetrahydrofuran (20 ml), and benzoyloxycarbonyl succinimide (1.84 g, 1.1 eq) was added and stirred at room temperature for 20 hours. The solvent was evaporated, and the residue was dissolved in dichloromethane, washed with water, and the organic phase was collected and dried over Na2SO4. The crude product 2b was obtained by evaporation of the solvent and purified by HPLC (gel permeation chromatography). The product was 1.86 g, with a yield of 98%. ESI-MS m / z calculated for [C 14 H 22 NO5] + (M+H) + :284.14,found:284.13.

[0134] 2. Synthesis of chemical molecule 3b

[0135] Phosphorus oxychloride (4.74 g, 1.25 eq) was dissolved in dichloromethane (10 ml) and stirred under ice bath at 0°C. 2b (7 g, 1 eq) prepared in the above step was dissolved in dichloromethane (10 ml), triethylamine (33.3 g, 1.33 eq) was added, and the solution was slowly added dropwise to the above phosphorus oxychloride solution using a constant pressure funnel, and stirred at room temperature for 1 hour. Pyridine (15.63 g, 8 eq) and choline p-toluenesulfonate (12.77 g, 2 eq) were slowly added under ice bath at 0°C, and stirred at 0°C for 2 hours. The reactants were stirred at room temperature for 24 hours. Water (1 ml) was added and stirred at room temperature for 1 hour. The solvent was evaporated, the residue was dissolved in anhydrous methanol, and the solvent was evaporated to dryness. This was repeated 2-3 times to obtain the crude product 3b, which was purified by HPLC (gel permeation chromatography). The product was 10.53 g, with a yield of 95%, and ESI-MS m / z calcd for [C 19 H 34 N2O8P] + (M+H) + :449.20,found:449,21.

[0136] 3. Synthesis of chemical molecule 4b

[0137] The 3b (11 g, 1 eq) prepared in the above step was dissolved in anhydrous methanol (50 ml), palladium / carbon (0.5 g) was added, and the mixture was stirred in a hydrogenation apparatus for 20 hours. The solution was filtered and the solvent was evaporated to obtain the crude product 4b without purification. The product was 10.53 g, with a yield of 99%. ESI-MS m / z calculated for [C 11 H 27 N3O6P] + (M+H) + :328.16,found:328.17.

[0138] 4. Synthesis of chemical molecule 5b

[0139] The 4b (260 mg, 1 eq) prepared in the above step was dissolved in anhydrous methanol (25 ml), and dibenzocyclooctyne-N-hydroxysuccinimide ester (400 mg, 1.2 eq) was added. The mixture was stirred at room temperature for 20 hours. The solvent was evaporated to obtain the crude product 5b, which was purified by HPLC (gel permeation chromatography). The product was 295.83 mg, with a yield of 90%. ESI-MS m / z calculated for [C 13 H 29 N5O7P] + (M+H) + :398.17,found:398.18.

[0140] Example 5

[0141] This example provides a functional material, which is different from Example 4 in that the structural formula of compound B is as follows:

[0142]

[0143] The preparation route is as follows:

[0144]

[0145] 1. Synthesis of chemical molecule 2c

[0146] Compound 1c (4.55 g, 1 eq) was dissolved in anhydrous ethanol (150 ml), di-tert-butyl dicarbonate (13 g, 1.2 eq) was added, and the mixture was stirred at room temperature for 3 hours. The solvent was evaporated, and the residue was dissolved in ethyl acetate, washed with water, and the organic phase was collected and dried over Na2SO4. The crude product 2c obtained by solvent evaporation did not need to be purified. The product was 9.50 g, with a yield of 100%. ESI-MS m / z calcd for [C8H 18 NO4] + (M+H) + :192.12,found:192.13.

[0147] 2. Synthesis of chemical molecule 3c

[0148] Powdered potassium hydroxide (3.05g, 5eq) was dissolved in anhydrous tetrahydrofuran (15ml) and stirred in an ice bath at 0℃. 2c (2.06g, 1eq) prepared in the above step was dissolved in anhydrous tetrahydrofuran (10ml), and slowly added to the above potassium hydroxide solution using a constant pressure funnel, and stirred in an ice bath for 15 minutes. Propyl bromide (4.7ml, 5eq) was slowly added, and the mixture was reacted in an ice bath at 0℃ for 5 minutes, and then returned to room temperature and stirred for 13 hours. Water (100ml) was added to dissolve the solid, and the mixture was extracted with dichloromethane, the extract was filtered, washed with water, the organic phase was collected, dried with Na2SO4, and the solvent was evaporated to obtain the crude product 3c, which was purified by HPLC (gel permeation chromatography). The product was 2.74g, with a yield of 95%, and ESI-MS m / z was calculated for [C 14 H 22 NO4] + (M+H) + :268.15,found:268.16.

[0149] 3. Synthesis of chemical molecule 6b (intermediate product)

[0150] 4b (300 mg, 1 eq) prepared in Example 4 was dissolved in anhydrous methanol (25 ml), succinimidyl azidoacetate (226.9 mg, 1.2 eq) was added, and the mixture was stirred at room temperature for 20 hours. The solvent was evaporated to obtain a crude product 6b, which was purified by HPLC (gel permeation chromatography). The product was 516.81 mg, with a yield of 90%. ESI-MS m / z calculated for [C 30 H 41 N3O8P] + (M+H) + :602.26,found:602.25.

[0151] 3. Synthesis of chemical molecule 4c

[0152] 6b (660 mg, 2.4 eq) prepared in the above step was dissolved in tetrahydrofuran aqueous solution (V / V=4:1), copper iodide (30 mg, 0.2 eq) and N,N-diisopropylethylamine (165 mml, 1.2 eq) were added, stirred at room temperature for 15 minutes, and then 3c (200 mg, 1 eq) was added, and stirred at room temperature for 24 hours. The crude product obtained by evaporation of the solvent was purified by HPLC (gel permeation chromatography). The product was 635.67 mg, with a yield of 80%, and ESI-MS m / z calculated for [C 40 H 78 N 11 O 18 P2] + (M+H) + :1061.49,found:1061.50.

[0153] 4. Synthesis of chemical molecule 5c

[0154] The 4c ​​(360 mg, 1 eq) prepared in the above step was dissolved in a mixed solution of hydrochloric acid (2.8 ml) and 1,4-dioxane (10 ml) and stirred at room temperature for 30 minutes. Sodium hydroxide (1 M) was added to adjust the pH to 7. The solvent was evaporated to obtain the crude product 5c which was purified by HPLC (gel permeation chromatography). The product was 326.40 mg, with a yield of 100%. ESI-MS m / z calculated for [C 35 H 70 N 11 O 16 P2] + (M+H) + :962.44,found:962.45.

[0155] 5. Synthesis of chemical molecule 6c

[0156] 5c (360 mg, 1 eq) prepared in the above step was dissolved in anhydrous methanol (25 ml), dibenzocyclooctyne-N-hydroxysuccinimide ester (331.3 mg, 2.2 eq) was added, and stirred at room temperature for 20 hours. The crude product obtained by evaporation of the solvent was purified by HPLC (gel permeation chromatography). The product was 402.49 mg, with a yield of 85%. ESI-MS m / z calculated for [C 54 H 83 N 12 O 19 P2] + (M+H) + :1265.53,found:1265.54.

[0157] Example 6

[0158] This example provides a titanium implant, and its structural schematic diagram is as follows Figure 2 As shown. The titanium implant prepared in the embodiment of the present invention has a super-hydrophilic surface coating composed of a DOPA module derived from marine mussels as a binder and a phosphatidylcholine super-hydrophilic head structure (PC module), and is constructed by the chelation of the DOPA module with the titanium substrate and the "Click reaction" of the surface modification groups between the two modules to finally form a coating structure, thereby providing a titanium implant surface with a super-hydrophilic coating.

[0159] The raw materials for its preparation are as follows: titanium base material, dopa derivative and compound B. The specific preparation process is as follows:

[0160] 1) Pretreatment of titanium substrate material: A titanium sheet with a diameter of 10 mm and a thickness of 2 mm was polished to 2000 mesh with sandpaper in sequence, and then ultrasonically cleaned with acetone, alcohol, and deionized water for 10 min in sequence, and dried naturally in the shade.

[0161] 2) Take the DOPA derivative (also called "grafted molecule", 0.1 mg) prepared in Example 1, dissolve it in water (1 ml) under ultrasonic environment, and prepare a DOPA aqueous solution (0.1 mg / ml); similarly, take the compound B (also called "superhydrophilic molecule", 0.1 mg) prepared in Example 5, dissolve it in water (1 ml) under ultrasonic environment, and prepare a PC aqueous solution (0.1 mg / ml).

[0162] 3) "One-step method": the operation process is as follows Figure 3 As shown, the DOPA-PC module was constructed by chemical synthesis and directly grafted onto the Ti surface in one step. Specifically, the DOPA aqueous solution and the PC aqueous solution were mixed and stirred at room temperature for 4 hours to obtain a DOPA-PC combined module solution, the pretreated titanium substrate material was immersed in the DOPA-PC solution for 24 hours, the surface was washed with sterile water for 3 times, and naturally dried in the shade to obtain a material with super hydrophilic properties.

[0163] The super-hydrophilic material can also be prepared by the "two-step method", the operation process is as follows Figure 4 As shown, DOPA module and PC module are synthesized respectively. DOPA module is first grafted onto Ti surface, and then PC module is grafted via "Click reaction". The specific operation is as follows: the pretreated titanium substrate material is immersed in DOPA aqueous solution for 24 hours, the surface is washed with sterile water for 3 times, and the material is naturally dried in the shade, and then the material is immersed in PC aqueous solution for 24 hours, the surface is washed with sterile water for 3 times, and the material is naturally dried in the shade, and a material with super hydrophilic properties is obtained.

[0164] The titanium implant prepared in this example is denoted as "DOPA2-2".

[0165] Example 7

[0166] This example provides a titanium implant, which is different from Example 6 in that the grafted molecule adopts the DOPA derivative prepared in Example 2, and the superhydrophilic molecule adopts the compound B prepared in Example 4.

[0167] The titanium implant prepared in this example is denoted as "DOPA3-1".

[0168] Example 8

[0169] This example provides a titanium implant, which is different from Example 6 in that the grafted molecule adopts the DOPA derivative prepared in Example 2.

[0170] The titanium implant prepared in this example is denoted as "DOPA3-2".

[0171] Example 9

[0172] This example provides a titanium implant, which is different from Example 6 in that the grafted molecule adopts the DOPA derivative prepared in Example 3, and the superhydrophilic molecule adopts the compound B prepared in Example 4.

[0173] The titanium implant prepared in this example is denoted as "DOPA4-1".

[0174] Example 10

[0175] This example provides a titanium implant, which is different from Example 6 in that the grafted molecule adopts the DOPA derivative prepared in Example 3.

[0176] The titanium implant prepared in this example is denoted as "DOPA4-2".

[0177] Test Example 1

[0178] In this example, the wettability of the titanium implant surface prepared in Examples 6 to 10 was tested. The wettability of different surfaces was tested using a contact angle tester. 2 μL of ultrapure water was added to the sample surface through a syringe to test the static water contact angle.

[0179] The test results of Example 10 are as follows Figure 5 As shown in the figure, it can be seen that the surface contact angle is less than 10°.

[0180] During the experiment, four samples were set up in each group as parallel controls, and their contact angles were measured and the average value was taken. The experiment was repeated three times.

[0181] The average test results of each titanium implant are summarized in a bar graph. Figure 6 shown.

[0182] As can be seen from the figure, the embodiment of the present invention can adjust the hydrophilicity of the material surface by changing the valence of the DOPA grafted molecules and the PC dynamic superhydrophilic molecules.

[0183] Test Example 2

[0184] In this example, the titanium implants prepared in Examples 6 to 10 were used to conduct osteoblast experiments.

[0185] After 7 days of osteogenic induction, the expression of osteogenic-related genes (ALP (alkaline phosphatase), Opn (osteopontin), and Runx2 (Runx-related transcription factor 2)) on each titanium implant sample was analyzed by real-time polymerase chain reaction (RT-PCR) using the Bio-Rad CFX 96Real-Time. The specific operation was as follows: Total RNA from mesenchymal cells on the sample was extracted using a kit. The purity and concentration of RNA were determined using a spectrophotometer to ensure that the A260 / A280 ratio was around 2 to ensure the quality of RNA. The extracted RNA was reverse transcribed into cDNA. Reverse transcriptase and specific primers were used to react to convert the RNA template into a more stable and amplifiable DNA form. Specific primers for ALP, Opn, and Runx2 genes were designed. The primer length is generally 20-25bp, the Tm value is around 60°C, and the amplified fragment length is recommended to be 150-250bp. Configure the PCR reaction system, including SYBRGreen dye, upstream primer, downstream primer, dNTP, Taq enzyme and cDNA template. The PCR reaction conditions are usually: 93℃ pre-denaturation for 2 minutes, then 93℃ for 1 minute, 55℃ for 2 minutes, for a total of 40 cycles. During the PCR amplification process, a real-time PCR instrument is used to monitor the fluorescence signal in real time to determine the cycle threshold (Ct) value. Use professional software to analyze the data, calculate the Ct value of each sample, and perform relative quantitative analysis of gene expression.

[0186] To ensure the reliability of the results, each sample should be subjected to at least three biological replicates and three technical replicates. Taking the test results of DOPA4-PC2 prepared in Example 10 as an example, the test results are summarized in a bar graph, as shown in FIG. Figure 7 shown.

[0187] As can be seen from the figure, the titanium implant prepared by the embodiment of the present invention can promote bone tissue formation. The test results of other titanium implants are similar, and they are not shown one by one to avoid redundancy. The embodiment of the present invention is based on the concept of bionic articular cartilage extracellular matrix, constructs the super-hydrophilic head of the phosphatidylcholine molecule on the surface of the titanium-based material, and then forms a super-hydrophilic surface coating to achieve a super-hydrophilic effect on the surface of the bone implant. The embodiment of the present invention prepares a Ti implant surface interface structure with a super-hydrophilic coating, and the super-hydrophilic coating on the surface is used to promote bone integration.

[0188] Among them, in the preparation process of the grafting module: the key module Fmoc-DOPA intermediate is synthesized from the commercial raw material DOPA through multi-step group operation, and after amide condensation to derive the azide side chain, the grafting molecule precursor is obtained through the reaction cycle of "removal of Fmoc-amide condensation", and then the Fmoc, propylidene and other protective groups on the precursor are removed to obtain a series of grafted molecules. Synthesis and preparation of superhydrophilic module: Starting from the commercial raw material DBCO-COOH, after amide condensation, the key intermediate is obtained by extending the connecting arms of different valences, and then the phosphatidylcholine structure is constructed through multi-step reactions with reagents such as trichloride and choline to obtain superhydrophilic molecules. ③ "Titanium substrate-grafted molecule-superhydrophilic molecule" self-assembly: The titanium implant / titanium sheet is immersed in the DOPA grafting module molecule and the superhydrophilic module molecule solution to complete the construction of the superhydrophilic implant surface coating.

[0189] In summary, the titanium implant of the present invention is mainly prepared from DOPA from marine mussels as a grafted molecule as an adhesive, and the phosphatidylcholine amphiphilic molecule characterizes the superhydrophilic property. Both have good biocompatibility, can better absorb water, help osteoblasts to quickly gather and adhere to the implant surface, and promote bone integration. The superhydrophilic implant prepared by the present invention utilizes the amphiphilic molecular characteristics to achieve the purpose of superhydrophilicity, and the monolayer formed by the self-assembly technology has the advantages of simple synthesis, high uniformity, precise functionalization, and reduced interference with surrounding tissues. It is particularly suitable for occasions with high requirements for coating thickness and uniformity. The present invention proposes the construction of a superhydrophilic surface from the perspective of structural bionics, which can not only imitate the self-cleaning surface (such as lotus leaves) in nature, but also keep the surface clean and functional. At the same time, a water film can also be formed on its surface to reduce the friction resistance of the fluid on the surface and improve the lubrication effect. Further, the present invention can also be based on the synthesis of different valence structural molecular modules, and the molecular modules of different valences are freely assembled to adjust the hydrophilicity of its surface interface. The present invention forms a super-hydrophilic surface coating by self-assembly of two chemical molecular groups. Therefore, the product of the present invention can be applied to the surfaces of implants of different materials, different shapes and different application parts, solving the problem of limited material selection and application scenarios of traditional implant surface activation methods.

[0190] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A dopa derivative, characterized in that: It has the following structural formula: In the formula, R0 is selected from a group capable of undergoing a copper-free click chemistry reaction; R1 is selected from AcNH-; a is selected from an integer of 2 to 6; and b is selected from an integer of 1 to 6.

2. The dopa derivative according to claim 1, characterized in that: The DOPA derivative has at least one of the following characteristics: 1) a is selected from an integer of 2 to 4; 2) b is selected from an integer of 1 to 2; 3) R0 is selected from at least one of an azido group or an oxynitrile group.

3. The dopa derivative according to claim 2, characterized in that: The DOPA derivative has one of the following structural formulas:

4. The method for preparing a dopa derivative according to any one of claims 1 to 3, characterized in that: The steps include: S1, reacting compound C containing an amino protecting group R4 with compound D to obtain intermediate 1, and removing the amino protecting group R4 in the intermediate to obtain intermediate 2; S2, adding compound C to react intermediate 2 with compound C; S3, repeat the operation of step S2 c times; S4, after acetylation reaction and removal of the propylidene group, the DOPA derivative is obtained; Wherein, the structural formula of compound C containing amino protecting group R4 is as follows: The structural formula of compound D is as follows: c=a-2.

5. The preparation method according to claim 4, characterized in that: R4 is selected from at least one of Fmoc, Alloc or Teoc.

6. A functional material, characterized in that: The raw material for preparing the functional material includes compound A, and the compound A is the dopa derivative as claimed in any one of claims 1 to 3.

7. The functional material according to claim 6, characterized in that: The raw materials for preparing the functional material also include compound B, and the compound B has the following structural formula: In the formula, R2 is a group that can undergo copper-free click chemistry reaction with R0; R3 is selected from alkylene, alkylene containing amide bonds, PEG containing amide bonds, d is selected from an integer of 1-4, and e is selected from an integer of 1-5.

8. The functional material according to claim 7, characterized in that: The R2 is selected from at least one of dibenzocyclooctyne, diaryl azacyclooctyne, bifunctional fluorinated cyclooctyne or cyclooctyne; preferably, the compound B has one of the following structural formulas:

9. The functional material according to claim 7, characterized in that: The molar ratio of compound A to compound B in the raw materials for preparing the functional material is 1 to 4:

1.

10. An implant, characterized in that: The implant comprises the dopa derivative according to any one of claims 1 to 3 or the functional material according to any one of claims 6 to 8.

11. The implant according to claim 10, characterized in that: The raw materials for preparing the implant further include a base material, and the base material includes at least one of a polymer-based material, a ceramic-based material, and a metal-based material.

12. A method for preparing an implant, characterized in that: The raw materials for preparing the implant include a base material, compound A and compound B, and the preparation method includes the following steps: S1, taking a base material, placing the base material in a solution containing compound A, reacting to obtain an intermediate material; S2, adding a solution containing compound B to allow compound B to undergo a click chemical reaction with molecular groups on the surface of the intermediate material to obtain the implant; Wherein, the compound A is a dopa derivative as claimed in any one of claims 1 to 3, and the compound B has the following structural formula: In the formula, R2 is a group that can undergo copper-free click chemistry reaction with R0; R3 is selected from alkylene, alkylene containing amide bonds, PEG containing amide bonds, d is selected from an integer of 1-4, and e is selected from an integer of 1-5.

13. A method for preparing an implant, characterized in that: The raw materials for preparing the implant include a base material and the functional material as claimed in claim 7, and the preparation method includes the following steps: placing the base material in a solution containing the functional material, reacting, and obtaining the implant.

14. An orthopedic titanium medical device, characterized in that: It includes a titanium-based material and also includes the functional material according to any one of claims 6 to 8, wherein the titanium-based material includes at least one of titanium, titanium alloy or titanium dioxide.

Citation Information

Patent Citations

  • Preparation method of environment-friendly superhydrophilic dental implant activated surface

    CN106823005A

  • Surface treatment process of 3D printed implant

    CN112974843A

  • Thin film vascular stent and biocompatible surface treatment

    WO2010102254A2

  • Methods of manufacturing superhydrophilic implants

    WO2013124693A1

  • Ultra-hydrophilic titanium implant, and surface treatment and storage methods thereof

    WO2013165051A1